"There Are Different Ways You Can Be Good at Math": Quantitative Literacy, Mathematical Modeling, and Reading the World. Issue 3 (21st April 2019) - Simic-Muller, K.
Abstract: This manuscript describes a quantitative literacy course focusing on issues of economic and racial justice, developed for a summer bridge program. The curriculum for the course, described in the manuscript, consisted of open-ended assignments that dealt with real-world issues and required basic modeling skills; whereas the culminating assignment was a final project about a community-based topic. The course helped students deepen their understanding of the issues addressed and strengthen their mathematical reasoning skills; and had a transformative effect on some students' perceptions of the usefulness of mathematics, of themselves as mathematics learners, and of their communities.